Biometric observations of newborn Crocodylus acutus (Cuvier, 1807) obtained in captivity in, Tumbes, Peru - Pérez, Oswaldo (2005)
In this paper, length and weigth measurements of 20 newborn Crocodylus acutus (Cuvier, 1807) hached in a pilot farm-bred of the aquaculture center La Tuna Carranza, Puerto Pizarro, Tumbes, Peru, in 2001 are presented. The information is compared with similar reports from others places.